The Integrin α2β1 (GPIa/IIa)-I-Domain Inhibits Platelet-Collagen Interaction - Depraetere, H; Wille, C; Gansemans, Y; Stanssens, P; Lauwereys, M; Baruch, D; De Reys, S; Deckmyn, H (Thrombosis and Haemostasis, 1997)
The integrin α2β1 is a major cellular receptor for collagen. The α2subunit contains an ± 200 amino acids inserted domain (I-domain) in the N-terminal region. A certain degree of homology exists between the I-domains found in integrins, collagen and the A-domains of vWF.The α2-I-domain encoding region (aa residues D145 to S334) was obtained by RT-PCR from mRNA of non stimulated human PBL’s. The primers were designed to introduce the necessary restriction sites for cloning of the DNA fragment in frame downstream of the malE gene, as well as a stop codon after the last triplet. The resulting construct pMAL-c2-α2-I allows the expression of the I-domain, fused to the C-terminus of maltose binding protein (mal). The α2-I-mal is purified from the bacterial extract by affinity chromatography on an amylose column.The purified α2-I-mal has been characterized by ELISA’s. The animal bound to immobilised collagen type I in a concentration dependent manner and could be blocked by the functional monoclonal anti-α2β1 antibody 6F1.The interaction of α2-I-mal with collagen furthermore is Mg2+- dependent since the binding was inhibited in the presence of 10 mM EDTA or 10 mM Ca2+ but sustained in the presence of 10 mM Mg2+.Finally, α2-I-mal itself was able to inhibit adhesion of washed platelets to collagen immobilised on a microtiterplate in a dose-dependent manner (α2-I-mal IC50:0.7 μ M) as well as platelet aggregation induced by collagen type I (α2-I-mal IC50: 0.7 μM).With these results we could confirm that the α2-I-domain represents the collagen-binding site of α2β1 and we furthermore could indicate that this domain is able to prevent platelet adhesion to collagen and collagen-induced platelet aggregation, pointing to the primordial role of α2-I-mal and hence of α2β1 in platelet-collagen interaction.